2022
DOI: 10.3389/fonc.2022.855519
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality imaging in lobular breast cancer: Differences in mammography, ultrasound, and MRI in the assessment of local tumor extent and correlation with molecular characteristics

Abstract: IntroductionInvasive lobular breast cancer (ILC) is a diagnostic challenge due to the diversity of morphological features. The objective of the study was to investigate the presentation and local extent of ILC using various imaging techniques and to assess the correlation between imaging and molecular profile.Materials and methodsWe reviewed 162 consecutive patients with ILC found on vacuum-assisted biopsy, who underwent evaluation of the lesion morphology and extent using ultrasound (US), mammography (MMG), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Various observations related to molecular immunophenotype and radiological features are described in the literature. While some authors have noted a difference between PgR expression and lesion appearance at MR, with PgR negative tumors occurring more frequently with larger lesions and without mass enhancement, other authors have found no association between molecular phenotype and MR appearance [ 13 , 18 ]. Some cancers, including DCIS, some invasive lobular carcinomas, and some other low-grade invasive tumors, may not show enhancement on MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Various observations related to molecular immunophenotype and radiological features are described in the literature. While some authors have noted a difference between PgR expression and lesion appearance at MR, with PgR negative tumors occurring more frequently with larger lesions and without mass enhancement, other authors have found no association between molecular phenotype and MR appearance [ 13 , 18 ]. Some cancers, including DCIS, some invasive lobular carcinomas, and some other low-grade invasive tumors, may not show enhancement on MRI.…”
Section: Discussionmentioning
confidence: 99%